Review: a comprehensive summary of a decade development of the recombinase polymerase amplification. Issue 1 (14th November 2018) - Li, Jia; Macdonald, Joanne; von Stetten, Felix
Abstract : RPA is a versatile complement or replacement of PCR, and now is stepping into practice. Abstract : Nucleic acid amplification has permeated every field in the life sciences since the introduction of the classic polymerase chain reaction (PCR) method in 1983. Yet, despite its fundamental reach, PCR has been constrained within the walls of a laboratory, due to its requirement for a sophisticated thermocycling machine, limiting external application in low-resource settings. New isothermal amplification strategies are seeking to break through traditional laboratory boundaries by providing nucleic acid replication at constant temperatures. Of these methods, recombinase polymerase amplification (RPA) is one of the fastest developing, experiencing rapid uptake and market, even though it was introduced comparatively late. Critically, RPA's technology potentiates highly accessible and sensitive nucleic acid amplification outside of laboratory, and even self-testing. Here we provide a comprehensive review of the equipment-free simplicity of RPA over its first decade of development. Our review includes key knowledge of RPA technology, such as its reaction components, mechanism, sensitivities and specificities, and distinctive detection methods. The review also provides know-how for developing RPA assays, and information about commercially available RPA reaction kits and accessories. We summarise critical RPA experimental tips and issues available through data mining the published literature, to assist researchers in mastering the RPA reaction. We also outline influential hotspots of RPA development, and conclude with outlooks for future development and implications for eclipsing PCR and further revolutionising the life sciences.